Respostas

2014-05-17T14:04:45-03:00
A)(3x+17)² = (3x)² + 2.3x.17 + 17²
                    9x²  +  102x  + 289


b)(14x-10)² = (14x)² - 2.14x.10 + 10²
                   196x² -280x + 100


c)(3x+17)(3x-17) = 9x² -51z + 51x - 289
                                9x² - 289


d)(14x-10)(14x+10) = 196² +140x -140x - 100
                                  196x² -100



e)x²-225=0  onde a=1   b=0   c=-225

Δ=b²-4.a.c
Δ=0²-4.1.(-225)
Δ=0+900
Δ=900  ⇒ raiz de 900 é 30

x'=0+30    30
   ¨¨¨¨¨¨¨¨¨= ¨¨¨¨¨¨ = 15
     2.1        2



x=0-30    -30
  ¨¨¨¨¨¨¨¨ = ¨¨¨¨¨¨¨= -15
    2.1        2                                S:(15,-15)





f)x²-10x+25=0        onde   a=1    b=-10   c=25


Δ=b²-4.a.c
Δ=(-10)²-4.1.25
Δ=100-100
Δ=0  ⇒ raiz de 0 é 0


x'=+10+0     10
    ¨¨¨¨¨¨¨¨¨¨ = ¨¨¨¨¨¨  = 5
        2.1        2

x"=+10-0      10
     ¨¨¨¨¨¨¨¨ =  ¨¨¨¨¨¨ = 5
       2.1         2                         S:(5, 5)


Espero ter ajudado, abraço.